Fluktuasi Tingkat Pendapatan Pengemudi Transportasi Konvensional: Disparitas Ekonomi terhadap Pengemudi Transportasi Online - Utomo, Aghniya Malika Putri; Alya, Dea; Muharram, Ragil; Mutia, Amanda; Assegaff, Nazli Naela (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the factors that cause fluctuations in income of conventional transportation drivers amidst the increasing existence of online transportation. This study uses a descriptive qualitative approach with a data collection method through interviews with several drivers in Bandung. The analysis technique used is a thematic analysis based on categorized interview data. The results of the study indicate that fluctuations in the income of conventional drivers are not only caused by direct competition with online transportation. But also, influenced by internal factors such as the age of the drivers, the majority of whom are advanced, limitations in the use of technology, and the assumptions of community groups that cause negative personal stigmas against online transportation drivers. Other factors such as consumer demand that tends to decrease for conventional transportation services, dependence on regular customers, non-strategic base locations, and financial distribution systems such as operational costs also affect the small net income received. Overall, this study shows that the problem of income fluctuations is closely related to social structures, technology, and economic resources that are not evenly distributed.